2010
DOI: 10.1007/s10565-010-9156-4
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin prevents in vitro auto-oxidative injury in human lymphocytes

Abstract: Upon mitogen sensitization, lymphocytes undergo proliferation by oxyradical-based mechanisms. Through continuous resting-restimulation cycles, lymphocytes accumulate auto-induced oxidative lesions which lead to cell dysfunction and limit their viability. Astaxanthin (ASTA) is a nutritional carotenoid that shows notable antioxidant properties. This study aims to evaluate whether the in vitro ASTA treatment can limit oxyradical production and auto-oxidative injury in human lymphocytes. Activated lymphocytes trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 45 publications
2
40
0
1
Order By: Relevance
“…Recently, Bolin et al [35] found that astaxanthin displayed interesting anti-inflammatory effects by preserving redoxsensitive and essential structures of human lymphocytes, which could be mainly deduced by the increased nitric oxide formation, the observed reduced O_ 2 À /H 2 O 2 production, and induced superoxide dismutase and catalase activities in parallel to lower indexes of oxidative injury in lipids and proteins. It was suggested that astaxanthin was potentially nutritional therapeutic agent for prevention/prophylaxy of immune-impaired diseases, such as type 2 diabetes, sepsis, and cardiovascular disorders [35].…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Bolin et al [35] found that astaxanthin displayed interesting anti-inflammatory effects by preserving redoxsensitive and essential structures of human lymphocytes, which could be mainly deduced by the increased nitric oxide formation, the observed reduced O_ 2 À /H 2 O 2 production, and induced superoxide dismutase and catalase activities in parallel to lower indexes of oxidative injury in lipids and proteins. It was suggested that astaxanthin was potentially nutritional therapeutic agent for prevention/prophylaxy of immune-impaired diseases, such as type 2 diabetes, sepsis, and cardiovascular disorders [35].…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“…It was suggested that astaxanthin was potentially nutritional therapeutic agent for prevention/prophylaxy of immune-impaired diseases, such as type 2 diabetes, sepsis, and cardiovascular disorders [35]. Macedo et al [36] showed that astaxanthin significantly reduced the production of pro-inflammatory cytokines, such as tumor necrosis factor-a and interleukin-6 in lipopolysaccharidestimulated neutrophils.…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“…ASTA may act as a strong antioxidant by donating the electrons and reacting with free radicals to convert them into a more stable product and terminate free radical chain reaction in a wide variety of living organisms [25,26]. In recent years, a major number of studies on ASTA have demonstrated its antioxidant effect, for example the quenching effect on singlet oxygen, a strong scavenging effect on superoxide, hydrogen peroxide, and hydroxyl radicals and an inhibitory effect on lipid peroxidation [27][28][29][30]. In addition, several other biologic activities of ASTA, including anti-cancer, anti-inflammatory, antidiabetic, immunomodulatory activities and a neuroprotective effect also have been reported [25,31].…”
Section: Contents Lists Available At Sciverse Sciencedirectmentioning
confidence: 99%
“…Moreover, other studies reported that ASTA was able to protect the cells toward the mutagen carbon tetrachloride, and consequently, inhibit the hepatic damage through suppression the peroxidation of the lipids and enhancing the antioxidants production as well as regulating the process of the inflammation [52].…”
Section: Effect Of H Pluvialis Extract On the Cytokines Levelmentioning
confidence: 98%